All-optical adaptive control of quantum cascade random lasers - S. Schönhuber (Nature Portfolio, 2020)
Tunable quantum cascade lasers can enable applications in multiple areas. Here, the authors demonstrate the adaptive control of the modes and emission spectra of quantum cascade random lasers through a spatially-tailored optical modulation of the active region.